К ПОСТРОЕНИЮ АНТРОПОЛОГИИ ПОСТИНДУСТРИАЛЬНОГО ОБЩЕСТВА - МАСАЛОВ, А. Г.; РАК, В. А. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
В статье рассматриваются направления и аспекты трансформациииндивидуальности в современном мире. Проанализированы основные антропологическиеконцепты «философии постиндустриализма». Анализируется идеологический аспекттеории информационного общества.Масалов О.Г., Рак В.А. ДО ПОБУДОВИ АНТРОПОЛОГІЇПОСТІНДУСТРІАЛЬНОГО СУСПІЛЬСТВА У статті розглядаються напрями таособливості трансформації індивідуальності у сучасному світі. Проаналізовано основніантропологічні концепти «філософії постіндустріалізму». Аналізується ідеологічнийаспект теорії інформаційного суспільства.Ключові слова: «постмодерн», інформаційне суспільство, постіндустріальнесуспільство, ідентичність, світогляд, ідеологія.Masalov A. G., Rak V. А. TO THE CONSTRUCTION OF ANTHROPOLOGY OFPOSTINDUSTRIAL SOCIETY The article is devoted to the directions and aspects oftransformation of a human’s individuality in the modern world. Actuality of the article isconditioned by the situation, when most works on this subject devoted to the technologies,economy and history, while a second-rate role is given to a person.The complex of futurology ideas, dedicated to the radical changes of society, cultureand a human under the influence of various technologies was certain as a philosophy ofpostindustrial society. On the basis of works of row of researchers (D. Bell, E. Toffler, M.Kastels, A. Negri, M. Khardt, J. Attali, A. Zinov'ev and others), basic anthropologicalkonceptions of “philosophy of postindustrialism” were analysed.The possible tendencies of transformation of a human were examined in the contextof fragmentary perception of reality, «demassification» of culture, permanent changes ofinformation context, penetration of electronic devices in everyday life, achievements of thegene engineering, transferring of social inequality to the global level.The contradictory tendencies in forming of social identity in the process ofinformative globalization were defined. The visible contradictions of the universalism andpluralism in information society are removed by transferencing them both in the sphere ofpure ideological, and political (through a copula «knowledge» – «power») paradigms,which applicable to the world of things and events depending on situation.The ideological aspect of theory of information society, as a component part ofdiskurs of power, was analysed in the context of situation of «the end of metanarrations»and in connection with concrete historical and cultural terms.Anthropological prognoses of futurology, considered as: a) a possible conseqence ofexistent tendencies (prognostic aspect); b) a condition of some groups and parts of societyand world on the whole (diagnostic aspect); c) the state of society, desired by some groups(project aspect).The basic konceptions which have a direct relation to the construction of theanthropology of postindustrial society were introducted: «a human as a commodity,creating itself»; «a human, as a product of genetic manipulations»; the koncept of «thekiborg»; «the new nomadism»; «a human in the chaos of information» (contextual«dividuum»).The derections of future actual researches are marked: connection betweeninteractiveness, as asymmetric phenomenon, language, as a tool of the derrivation ofmeanings, and a power, as a practical expression of the hierarchies of networks, major fromwhich are accessible to the limited number of individuals.Keywords: «postmodern», information society, postindustrial society, identity,«model of reality», ideology, «new nomadism», kiborg.